2011
DOI: 10.1371/journal.pcbi.1002201
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Dynamics upon Oligomerization Regulate Substrate Binding and Allostery in Amino Acid Kinase Family Members

Abstract: Oligomerization is a functional requirement for many proteins. The interfacial interactions and the overall packing geometry of the individual monomers are viewed as important determinants of the thermodynamic stability and allosteric regulation of oligomers. The present study focuses on the role of the interfacial interactions and overall contact topology in the dynamic features acquired in the oligomeric state. To this aim, the collective dynamics of enzymes belonging to the amino acid kinase family both in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 80 publications
(93 reference statements)
1
52
0
Order By: Relevance
“…Nonetheless, the fact that initial structures were found for the T and R forms of haemoglobin supported the notion that allostery as a general phenomenon might be understood, perhaps in all systems, if only the structures of the allosteric states could be determined. To that end, extensive molecular dynamics 33,46,47 and coarse-grained network simulation 20,48 (for those proteins in which rigid body motions could be proposed for the allosteric transition) further suggested that ‘allosteric mechanisms reliant primarily upon observable changes in the ensemble-average structure are common and may be dominant’ 20 . Although the discovery of an alternate ‘relaxed’ structure of haemoglobin by Arnone and co-workers 49 laid to rest the simple two-state view of allostery, at least for haemoglobin, not fully appreciated was the range of possible regulatory strategies that could be used if the full spectrum of binding and conformational states of proteins were to be harnessed.…”
Section: From Structures To Ensemblesmentioning
confidence: 99%
“…Nonetheless, the fact that initial structures were found for the T and R forms of haemoglobin supported the notion that allostery as a general phenomenon might be understood, perhaps in all systems, if only the structures of the allosteric states could be determined. To that end, extensive molecular dynamics 33,46,47 and coarse-grained network simulation 20,48 (for those proteins in which rigid body motions could be proposed for the allosteric transition) further suggested that ‘allosteric mechanisms reliant primarily upon observable changes in the ensemble-average structure are common and may be dominant’ 20 . Although the discovery of an alternate ‘relaxed’ structure of haemoglobin by Arnone and co-workers 49 laid to rest the simple two-state view of allostery, at least for haemoglobin, not fully appreciated was the range of possible regulatory strategies that could be used if the full spectrum of binding and conformational states of proteins were to be harnessed.…”
Section: From Structures To Ensemblesmentioning
confidence: 99%
“…We use an approach similar to that of Bahar and Chang to obtain a protein's monomeric form from the oligomeric assembly. For each protein, we extract only the first chain from the PDB file and consider it to be the isolated monomer ( normalMnormalonormalnnormalonormalmnormalerisolated) and when the same chain is in the oligomeric assembly, we refer to it as normalMnormalonormalnnormalonormalmnormaleroligomer.…”
Section: Methodsmentioning
confidence: 99%
“…Previously Voth et al, showed that the dimeric form of triosephosphate isomerase was required to obtain appropriate motions of the closing loop, while the monomer does not show such motions. Bahar et al investigated the low frequency normal modes accessible to an individual subunit of amino acid kinases in the monomeric and oligomeric forms and proposed that changes to the dynamics upon oligomerization facilitate allostery and ligand binding. A molecular dynamics simulation of tryptophan synthase revealed that in its monomeric form the enzyme is more rigid and cannot undergo conformational transitions that are seen after oligomerization .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the lowest modes are different from one oligomeric state to the other, where subunit-subunit motions make up the lowest energy modes in multimeric assemblies. Since monomers usually possess differences in conformation based on their oligomeric state, comparing monomers extracted from different states provides sufficient basis for observing changes in their dynamics [25]. Zen et al [91] compared the flexibility of interfacial residues in obligate and non-obligate dimers.…”
Section: Comparing Dynamics Between Different Oligomeric/multimeric Smentioning
confidence: 99%
“…Examples of comparative dynamics analysis include studying a set of proteins that represent various functional states of a given enzyme upon ligand-binding [19,20], evaluating the conservation of dynamics within a homologous protein family [21][22][23][24][25][26][27], or within a set of proteins that possess the same fold despite low sequence identity [28,29]. In a recent article, Cristian Micheletti comprehensively reviewed the use of dynamics as an aid for sequence and structure alignments of proteins [30].…”
Section: Introductionmentioning
confidence: 99%